A modified electrospark alloying method for low surface roughness - Ribalko, Alexander V.; Şahin, Orhan; Korkmaz, Kemal (Elsevier Science Sa, 2009)
A modified electrospark alloying method has been developed. The method allows the formation of deposits with low surface roughness compared to that of the conventional electrospark alloying method. It is based on the employment of a sequence of identical pulse groups. The process of electrospark deposition and the process of electrospark grinding were combined by forming pulse groups consisting of a high energy pulse for mass transfer from treating electrode to substrate and low energy pulses for grinding during deposition. Low as-deposited surface roughness was succeeded by properly selecting parameters of the pulses in a group and pauses between them. Experimental results revealed that the proposed method is useful in forming one-two layers of deposition. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alloying; Coating; Electrospark; Pulse groups; Roughness